The impact of applying quality in the examination of biology at the clinical forensic medicine clinic in Mecca - Abdulaziz.S.Emam; Yaseen.S.Natto; Khalil.I.Alqurashi; Mohammed.S.Alzahrani; Naif.G.Allahyani; Atef.S.Alsuwihri; Mohammed.O.Almalky; Mohammed.M.Alameer; Adel.M.Alhazmi; Fahad.A.Bakkari (International Journal of Medical Toxicology and Legal Medicine, 2024)
This current study aims to know the effect of applying quality standards in the medical refrigerator in examining biology, and the effect of employees applying quality standards at work in examining biology, the methods used in examining biology in a clinical forensic medicine clinic, what are the components of a clinical forensic medicine clinic. The questionnaire was prepared via Google Drive and distributed to all employees of the Forensic Medical Services Center in Mecca (administrators, technicians, and doctors). It was distributed to them via the social networking program (WhatsApp), and responses were obtained via email. It concluded that All procedures taken and implemented in the clinical forensic medicine clinic reflect the extent of precision and diligence in the work and the rate of application of quality is very high.